Seizures and Brain Regulatory Systems. Issue 3 (June 2015) - Sedigh-Sarvestani, Madineh; Blumenfeld, Hal; Loddenkemper, Tobias; Bateman, Lisa M.
<x xml:space="preserve">Abstract</x> Summary: Research into the physiologic underpinnings of epilepsy has revealed reciprocal relationships between seizures and the activity of several regulatory systems in the brain. This review highlights recent progress in understanding and using the relationships between seizures and the arousal or consciousness system, the sleep–wake and associated circadian system, and the central autonomic network.